Microstrucure and thermal features a-Si:H and nc-Si:H thin films produced by r.f. sputtering - Thaiyalnayaki, V. (2006)
Amorphous and nanocrystalline silicon thin films have been produced by reactive r.f. sputtering and their microstructure, optical and thermal properties were evaluated. A good correlation was found between the microstructure determined by Raman spectroscopy and X-ray diffraction and the thermal transport parameters